Assessment of cellular responses in three‐dimensional cell cultures through chemical exchange saturation transfer and 1H MRS. (21st May 2022) - Wu, Ssu‐Ting; Chen, Pin‐Chen; Tseng, Yu‐Hsien; Chen, Ting‐Hao; Wang, Yi‐Jiun; Tsai, Zong‐Lin; Lin, Eugene C.
Abstract : Metabolic responses to physiological changes have been detected using chemical exchange saturation transfer (CEST) imaging in clinical settings. Similarly to other MRI techniques, the CEST technique was based originally on phantoms from buffer solutions and was then further developed through animal experiments. However, CEST imaging can capture certain dynamics of metabolism that solution phantoms cannot model. Cell culture phantoms can fill the gap between buffer phantoms and animal models. In this study, we used 1 H NMR and CEST in a B 0 field of 9.4 T to investigate HEK293T cells from two‐dimensional (2D) cultures, three‐dimensional (3D) cultures, and 3D cultures seeded with cell spheroids. Two CEST dips were observed: the magnitude of the amine dip at 2.8 ppm increased during the incubation period, whereas the hydroxyl dip at 1.2 ppm remained approximately the same or modestly increased. We also observed a CEST dip at 2.8 ppm from the 2D culture responding dramatically to doxorubicin treatment. By cross‐validating with pH values and the concentrations of amine and hydroxyl protons extracted through 1 H NMR, we observed that they did not correspond to an increase in the amine pool. We believe that the denaturation or degradation of proteins from the fetal bovine serum increased the size of the amine pool. Although 3D culture conditions can be further improved, our study suggests that 3D cultures have the potential to bridge studies of solution phantoms and those on animals. Abstract : A 3D cell culture system has been established, which allows us to cross‐validate biological responses by 1 H NMR spectroscopy and chemical exchange saturation transfer (CEST). We observed the difference in the magnitudes of amine dips in CEST from control and doxorubicin‐treated (+DOX) cultures. By tuning the culture conditions, the 3D cell cultures could be utilized to mimic more physiological conditions for CEST validation in the future.